2017
DOI: 10.1111/apa.14152
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mood disorders and lithium exposure in utero were not associated with poor cognitive development during childhood

Abstract: This small, clinical cohort showed no significant association between mothers' prenatal exposure to lithium or mood disorders and their offspring's IQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…One child in this study was diagnosed with minor neurological dysfunction without clinical implications. A recent study compared the intelligence quotient (IQ) in children with in utero exposure to lithium (n = 20), non-exposed children of mothers with a mood disorder (n = 8) and controls (n = 11) and reported no difference in total, performance or verbal IQ (Forsberg et al 2017).…”
Section: Consequences For the Developing Childmentioning
confidence: 99%
“…One child in this study was diagnosed with minor neurological dysfunction without clinical implications. A recent study compared the intelligence quotient (IQ) in children with in utero exposure to lithium (n = 20), non-exposed children of mothers with a mood disorder (n = 8) and controls (n = 11) and reported no difference in total, performance or verbal IQ (Forsberg et al 2017).…”
Section: Consequences For the Developing Childmentioning
confidence: 99%
“…evaluated children whose mothers were treated with lithium during pregnancy when they reached four to five years of age. This small study showed no significant associations between the mothers’ prenatal exposure to lithium or mood disorders and their children's intelligence quotients .
…”
Section: Lithium Exposure In Utero Did Not Seem To Affect Cognitive Dmentioning
confidence: 58%
“…All eight studies included in this study were conducted in high-income countries, which limits the generalizability of the findings to other populations. The Finnish PREDO study [3] and the Swedish clinical cohort study [29] examined European Nordic populations. The French EDEN [12], and Irish O'Leary [32] studies comprised southern European populations, while the Dutch Generation R studies [30,33] comprised a multiethnic European population.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that found no significant associations in unadjusted or adjusted models are the Greek Rhea Study on prenatal depressive symptoms and child neurodevelopment [28], among 288 motherechild dyads, and a small Swedish study [29] of 39 children who were exposed to maternal mood disorders during pregnancy treated with lithium, to maternal mood disorders during pregnancy not treated with lithium, and who were not exposed to either one. The study that did not find associations and reported adjusted associations only is the multiethnic Dutch Generation R study among 5001 and 1994 motherechild dyads [30].…”
Section: Child Neurocognitive Outcomesmentioning
confidence: 99%